2016
DOI: 10.21070/pedagogia.v5i2.261
|View full text |Cite
|
Sign up to set email alerts
|

Pendekatan Problem Based Learning untuk Mengembangkan Kemampuan Berpikir Kritis Mahasiswa

Abstract: PENDAHULUANIlmu pengetahuan dan teknologi yang terus berkembang berpengaruh besar dalam dunia pendidikan. Hal ini membuat pelaku pendidikan meningkatkan strategi belajar mengajar untuk mendapatkan kualitas sumber daya manusia yang unggul. Strategi belajar mengajar yang baik memungkinkan dosen berinteraksi secara langsung dengan mahasiswa sehingga membuka kesempatan yang luas untuk pendalaman materi kepada mahasiswa. Selain itu strategi belajar mengajar dapat mendorong mahasiswa mengembangkan pengetahuannya ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
2
2
0
3
Order By: Relevance
“…It can be concluded that English language resource-based learning with Islamic content to develop the students' critical thinking of Mahad Al-Jamiah Putra UIN Salatiga effectively boosts the critical thinking of students/students. This is consistent with Zamzam (2016), who notes that one of the benefits of a problemsolving and experiential learning-based approach is that it focuses on students' information-processing skills. This information processing relates to how students engage with their surroundings, perceive problems, formulate concepts, and solve them.…”
Section: Discussionsupporting
confidence: 85%
“…It can be concluded that English language resource-based learning with Islamic content to develop the students' critical thinking of Mahad Al-Jamiah Putra UIN Salatiga effectively boosts the critical thinking of students/students. This is consistent with Zamzam (2016), who notes that one of the benefits of a problemsolving and experiential learning-based approach is that it focuses on students' information-processing skills. This information processing relates to how students engage with their surroundings, perceive problems, formulate concepts, and solve them.…”
Section: Discussionsupporting
confidence: 85%
“…Revealed their research that is, investigating the effects of Problem Based Learning (PBL) on preservice teacher performance on conceptual and quantitative problems regarding gas concepts. Analysis of the results of the study showed that students at the University of Muhammadiyah Malang experimental group had better performance on conceptual problems while there were no differences in student performance from quantitative problems [22]. The results of the study are discussed in terms of the effect of PBL on students' conceptual learning.…”
Section: Discussionmentioning
confidence: 86%
“…Problem-Based Learning (PBL) is a learning model oriented to using problems with real-world contexts that can practice critical thinking and problem-solving ability and a comprehensive understanding of a material concept (Arends, 2015;Herman, 2007). PBL can hone critical thinking skills because this model includes steps of activities that require students to carry out discussion, exploration, inquiry, discovery, and problem-solving (Galand et al, 2012;Morales-Mann & Kaitell, 2001;Sunaryo, 2014;Zamzam, 2016). In other words, the learning steps with this PBL model potentially can improve students' mathematical critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%